If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = -2x + 5 Reorder the terms: 8 = 5 + -2x Solving 8 = 5 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 8 + 2x = 5 + -2x + 2x Combine like terms: -2x + 2x = 0 8 + 2x = 5 + 0 8 + 2x = 5 Add '-8' to each side of the equation. 8 + -8 + 2x = 5 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 5 + -8 2x = 5 + -8 Combine like terms: 5 + -8 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5
| s-2r^2/2r | | 2w+10-8w=38 | | (-i)*(-7)*(-7i)= | | 2x+(x+3)=12 | | 9r=6+3r | | 4x^2+4y^2-16x+4y-60=0 | | 2m+10-7m=(4-m) | | Abs(6x+8)=9 | | 2w+10-(-8w)=38 | | 2x+2xy-1x= | | (4i)(6i)= | | x+2x+3+x=23 | | 5+4x(x-y)-y=0 | | x+2x+3x=23 | | 0=(3x+5)(3x-5) | | 10t-10=3t-1 | | -2.6=-1.9-7p | | 9+4=2(3-y) | | -2a-2=6 | | 2p^2-18=0 | | 3x-6=20-5x | | 8+4n=7n+8 | | 2.8=25.2 | | y=(-9*-9)+3 | | (-8i)(-5i)= | | 7y-5=5y-9 | | (2x)(5y)(-6)= | | 1/3-2/3(2x-5)=6x-11/3 | | 5x-4(3x-6)= | | 3a-1=2(a+4) | | -6(4x+1)=18-12x | | 8z=24+2z |